Laws that Protect Florida's Wildlife - Joe Schaefer; John Tucker; Maia McGuire (EDIS)
Revised! WEC-48, a 6-page fact sheet by Joe Schaefer, John Tucker, and Maia McGuire, summarizes laws and regulations at the Federal and State level that protect Florida’s wildlife, and how to report violations or wildlife emergencies. Published by the UF Department of Wildlife Ecology and Conservation, October 2008.